ELECTRODEPOSITION OF COPPER NANOWIRES IN POROUS POLYCARBONATE MEMBRANES - Karim, S.; Ali, G.; Ahmad, M.; Akhtar, J. I.; Maaz, K.; Durrani, S. K.; Hussain, M. A.; Saeed, K. (The Nucleus, 2020)
Copper nanowires of diameter 50 nm have been synthesized by electrochemical deposition in a nanoporous polycarbonate template. These membranes were created by ion irradiation of 30 Î¼m thick polycarbonate foils at UNILAC accelerator of GSI, Germany. Subsequent chemical etching of these foils were carried out in PINSTECH using 6M NaOH solution at 50 oC. A thin Cu layer on one side of these membranes, deposited by thermal evaporation, acted as cathode. A Cu rod was used as anode and the deposition was carried out potentiostatically at room temperature in a two electrode electrochemical cell. Subsequent to fabrication, the wires were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and UV-Visible spectroscopy.